Early virus-host interactions dictate the course of a persistent infection. - Brian M Sullivan; John R Teijaro; Juan Carlos de la Torre; Michael B A Oldstone (PLoS Pathogens, 2015)
Many persistent viral infections are characterized by a hypofunctional T cell response and the upregulation of negative immune regulators. These events occur days after the initiation of infection. However, the very early host-virus interactions that determine the establishment of viral persistence remain poorly uncharacterized. Here we show that to establish persistence, LCMV must counteract an innate anti-viral immune response within eight hours after infection. While the virus triggers cytoplasmic RNA sensing pathways soon after infection, LCMV counteracts this pathway through a rapid increase in viral titers leading to a dysfunctional immune response characterized by a high cytokine and chemokine expression profile. This altered immune environment allows for viral replication in the splenic white pulp as well as infection of immune cells essential to an effective anti-viral immune response. Our findings illustrate how early events during infection critically dictate the characteristics of the immune response to infection and facilitate either virus control and clearance or persistence.